A Quantitative Method to Monitor Reactive Oxygen Species Production by Electron Paramagnetic Resonance in Physiological and Pathological Conditions. (12th October 2014) - Mrakic-Sposta, Simona; Gussoni, Maristella; Montorsi, Michela; Porcelli, Simone; Vezzoli, Alessandra
Abstract : The growing interest in the role of Reactive Oxygen Species (ROS) and in the assessment of oxidative stress in health and disease clashes with the lack of consensus on reliable quantitative noninvasive methods applicable. The study aimed at demonstrating that a recently developed Electron Paramagnetic Resonance microinvasive method provides direct evidence of the "instantaneous" presence of ROS returning absolute concentration levels that correlate with "a posteriori" assays of ROS-induced damage by means of biomarkers. The reliability of the choice to measure ROS production rate in human capillary blood rather than in plasma was tested (step I). A significant (P < 0.01 ) linear relationship between EPR data collected on capillary blood versus venous blood (R 2 = 0.95 ), plasma (R 2 = 0.82 ), and erythrocytes (R 2 = 0.73 ) was found. Then (step II) ROS production changes of various subjects' categories, young versus old and healthy versus pathological at rest condition, were found significantly different (range 0.0001–0.05 P level). The comparison of the results with antioxidant capacity and oxidative damage biomarkers concentrations showed that all changes indicating increased oxidative stress are directly related to ROS production increase. Therefore, the adopted method may be an automated technique for a lot of routine in clinical trials.